PENGEMBANGAN LEMBAR KERJA MAHASISWA BERBASIS MODEL PREDICT-OBSERVE-EXPLAIN (POE) PADA MATERI SUHU DAN KALOR - Robiyati Robiyati; Boby Syefrinando; Fibrika Rahmat Basuki (Physics and Science Education Journal (PSEJ), 2023)
This study aims to determine the characteristics of student worksheets based on the POE model on temperature and heat material, determine the validity of student worksheets based on the POE model on temperature and heat material, find out student responses to student worksheet tests based on the POE model on temperature and heat material. This research is a development research (Research and Development) that uses a 4-D model. This research phase includes Define, Design, Develop and Disseminate. The subjects in this study were material experts, media experts, and language experts as well as students who had completed Basic Physics I course consisting of 8 students. The data collection instruments used were expert validation sheets and student questionnaires. Data validation results and student responses were analyzed descriptively. The product developed is in the form of student worksheets that use the POE model syntax on temperature and heat material. The experiments contained in the LKM are the effect of heat on object temperature, the application of the black principle, heat transfer by conduction, and convection. The results of the material expert validation are 100% in the very good category. The validation results by media experts were 93.84% in the very good category. The validation results of language experts were 91.42% in the very good category. The test results of student respondents on the developed student worksheets were 91.1% in the very good category. Based on the validation results of several experts and supported by the results of the respondents, it can be concluded that student worksheets based on the POE model on temperature and heat are appropriate to use.